Attitudes toward depression among Ecuadorian physicians using the Spanish-validated version of the Revised Depression Attitude Questionnaire (R-DAQ) - José Alejandro Valdevilla Figueira; Hans Mautong; Genesis Camacho L; Michelle Cherrez; Carlos Orellana Román; Geovanny Efraín Alvarado-Villa; Zouina Sarfraz; Azza Sarfraz; Arjola Agolli; María José Farfán Bajaña; Emanuel Vanegas; Miguel Felix; et al. (BMC Psychology, 2023)
Abstract Purpose Depression is inadequately recognized and managed, and physicians’ attitudes toward this condition and its treatment may play a part in this. This study aimed to assess Ecuadorian physicians' attitudes toward depression. Methods This was a cross-sectional study conducted using the validated Revised Depression Attitude Questionnaire (R-DAQ). The questionnaire was delivered to Ecuadorian physicians, and the response rate was 88.8%. Results 76.4% of participants had never received previous training in depression, and 52.1% of them indicated neutral or limited professional confidence when dealing with depressed patients. More than two-thirds of the participants reported an optimistic attitude toward the generalist perspective of depression. Conclusion Overall, physicians in Ecuador's healthcare settings were optimistic and held positive attitudes toward patients with depression. However, a lack of confidence in the management of depression and a need for ongoing training were found, especially among medical professionals who are not in daily contact with patients with depression.